Gazdasági szereplők és magatartások - Lengyel, György (Szociológiai Szemle, 2024)
The paper investigates the groups of entrepreneurs and employees. One of the crucial developments o f the social structure in the ‘90s is the emergence of an entrepreneurial class o f some 700 000. The developments, however, are contradictory in many and illusory in some respects. Less than half of the entrepreneurial class is characterized by profit-oriented calculative behaviour, by the separation of household and business, and by investing rather than consuming profit. Between 1993 and 1996 on-third of the small enterprises closed down. Survival is more frequent am ong forced entrepreneurs than among those who tried to realize their market ideas, since the latter are often part-time businesses which can be given up more easily. Enterpreneurial inclinations are on the decline, the arguments against entrepreneurship have shifted from a mentality of risk avoidance to shortage of capital. Private property, the tertiary sector and the inactive population have risen to predominance. Moreover, a new dual structure has evolved in economy, the dividing line being drawn between the small ventures and large enterprises. While earlier the first and second economies overlapped, as the persons acting in both were the same, now the actors are different in the two halves. The internal labour market is accessible to some one-fifth of job-takers, characterizing mostly the by large enterprises and institutions, especially in finance. However, fears of unemployment are considerably increasing in other intellectual and white-collar groups.